Modelling stock selection in Malaysia based on data envelopment analysis (DEA) / Md Khairu Amin Ismail - Ismail, Md Khairu Amin (Institute of Graduate Studies, UiTM, 2014)
and abundant empirical works have looked at this issue. Nevertheless, there is very limited empirical evidence that employs DEA in stock selection. Therefore, the main purpose of the study is to apply DEA models on stock selection of Malaysian stocks. The scope of the study incorporates all firms of the five sectors of Bursa Malaysia Main Market, which are consumer, industrial, property, plantation, and trading & services. Two DEA models, technicalefficiency and super-efficiency, are utilized in modeling the DEA stock selection in Malaysia. Stock selection takes place during various economic conditions, specifically sideway-trend, upward-trend and downward-trend, covering from 1998 to 2005. The ex-post period of portfolio performance is evaluated based on 12-month (short-term) and 36-month (long-term) holding periods. The empirical findings show that, during sideway-trend selection, on average, both the DEA super-efficiency and technical-efficiency portfolios produce significantly positive abnormal returns over the long-term.